Physico-chemical properties of spray-dried red pitaya (Hylocereus polyrhizus) peel powder during storage - Ee, Shu Chee; Bakar, Jamilah; Syed Muhammad, Sharifah Kharidah; Mat Hashim, Dzulkifly; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The physico-chemical properties of spray-dried pitaya peel powders kept at accelerated (45 ± 2°C) and room temperature (28 ± 2°C) for 14 weeks and 6 months, respectively were evaluated. Changes in physico-chemical properties of the peel powder were used as indicators of stability, while changes of the betacyanin pigment retention was used to calculate the shelf-life of the powder. Storage temperatures significantly (p < 0.05) affected all the studied parameters and Hunter a value had the most significant change. The pigment retention of peel powder was approximately 87% at 45°C and 89% at room temperature storage. Degradation of betacyanin pigment in the powder followed the first order reaction kinetics with the half-life (t1/2) of approximately 76 weeks at 45°C and 38 months at 28°C. The spray-dried pitaya peel powder had a solubility of 87 to 92% and low in powder hygroscopicity. The final Aw of the powder did not exceed 0.6 for both storage temperatures.